RESPON PERTUMBUHAN DAN PRODUKSI BAWANG MERAH (Allium ascalonicum L.) TERHADAP PEMBERIAN PUPUK NPK DAN KOMPOS KULIT BUAH KOPI - Afriadi Simanjuntak; Ratna Rosanty Lahay; Edison Purba (Jurnal Agroekoteknologi, 2013)
Application of inorganic fertilizers continuously without the use of organic fertilizers has caused the degradation of agricultural land. The negative impacts caused by land degradation is a decline in agricultural yield, such as the yield of shallot. A solution to solve this problem is to combination inorganic with organic fertilizers. Coffee pulp compost is one of the example of organic fertilizers. So, the research was conductedto investigate combination of NPK fertilizer and coffee pulp compost on growth and production of shallot which is use Randomized Block Design withtwofactors. Firstfactor is NPK fertilizer (0, 150,300, 450kg/ha) and thesecondfactor is coffee pulp compost (0,5, 10, 15 ton/ha).The results showed that the treatment of NPK fertilizer significantly affect the plant height 3,5,6 weeks after planting and production per plot.NPK at 150 kg/ha can increase production by 15.32% compared with no fertilization.Coffee pulp compost treatment significantly affect the production per plot.Compost at 10 ton/ha can increase production by 10.26% compared to without giving compost. The interaction between the NPK fertilizer and coffee pulp compost non significantly affect to all parameters.